2017
DOI: 10.15208/beh.2017.27
|View full text |Cite
|
Sign up to set email alerts
|

Community-based enterprise export strategy success: Thailand’s OTOP branding program

Abstract: Thailand's One Tambon One Product (OTOP) branded handicraft and food export program in 2016 reached nearly US$3billion, with products coming from approximately 6,000 community-based enterprises (CBE) and small-medium enterprises (SME) countrywide. The OTOP movement is a global program, with communities in China, Malawi, South Africa, Thailand, Laos, and the Philippines. This study examined the influences of perceived quality, competitiveness, trust, and distribution satisfaction on entrepreneurial export perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In addition to the value creation and proposition of the product, Nanthasudsawaeng (2019) reported that the key activities, key Resources, and cost structure are also the important factor affecting the performance improvement of the OTOP. For example, Sitabutr & Deebhijarn (2017) and Sitabutr & Deebhijarn (2018) revealed that OTOP product brands are not only influenced by perceived quality. Competitiveness, trust, and distribution satisfaction also impact business performance.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the value creation and proposition of the product, Nanthasudsawaeng (2019) reported that the key activities, key Resources, and cost structure are also the important factor affecting the performance improvement of the OTOP. For example, Sitabutr & Deebhijarn (2017) and Sitabutr & Deebhijarn (2018) revealed that OTOP product brands are not only influenced by perceived quality. Competitiveness, trust, and distribution satisfaction also impact business performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This operation and supply chain concept helps increase the business operation and consumer satisfaction of the OTOP and hence the sales. Sitabutr & Deebhijarn (2017) reported that consumer satisfaction with the OTOP product and brand could be attributed to perceived quality, competitiveness, trust, and distribution satisfaction. (Nanthasudsawaeng, 2019) also reported that the key business activities and cost structure are important factors affecting the performance improvement of entrepreneurs in addition to the product's value proposition.…”
Section: Introductionmentioning
confidence: 99%
“…Mentoring program in intensive workforce development, small business assistance from the government (Craft et al, 2020). The role of craft design as a sustainable craft development with problem-solving in the future of the craft product itself (W. T. Li et al, 2019).. Branding influences quality competitiveness and customer trust as an export strategy of artisans (Sitabutr & Deebhijarn, 2017). displays exhibitions to communicate objects' content and consumers get complete information (Fuadianti et al, 2020).…”
Section: Displaymentioning
confidence: 99%
“…In the past, there has been literature on the trust relationship between exporters and importers (Katsikeas et al 2009; Saleh et al 2013; Leonidou et al 2014) and between trust and export performance (Solberg and Nes, 2002; Gulati and Nickerson, 2008; Styles et al 2008; Bloemer et al 2013; Lin et al 2014; Chang and Fang, 2015; Matanda et al 2016; Ismail et al 2017; Sitabutr and Deebhijarn, 2017; Hirshberg and Shoham, 2017) (Table II).…”
Section: Theoretical Background and Literature Review On Export Promotion Related To Export Performancementioning
confidence: 99%